PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN BAAMBOOZLE PADA PEMBELAJARAN PENDIDIKAN PANCASILA MATERI PANCASILA DALAM KEHIDUPANKU DI KELAS V SDN 101776 SAMPALI T.A 2025/2026 - Cantika Sianipar, Naomi; Apiek Gandamana (STKIP Subang, 2026)
This research was carried out with the aim of knowing the level of feasibility, practicality, and effectiveness of Learning Media assisted by Baamboozle. This type of research is R&D with the ADDIE development model. The subjects of this study were 20 students consisting of 9 male students and 11 female students. Data collection techniques in this research consisted of interviews, questionnaires, and tests. The instruments used in this research include interview instruments, expert instruments (questionnaire, material, and media), practicality instruments (teacher response questionnaire), and student learning outcomes tests. Data analysis techniques are qualitative data and quantitative data. The results showed that the feasibility of the product got a percentage of 80%. The results of product practicality get a percentage of 80%. The results of product effectiveness obtained a result of 0.44. It can be concluded that the learning media assisted by Baamboozle is declared feasible, practical, and effective in improving the learning outcomes of fifth grade students in Pancasila Education subjects. It can be concluded that Baamboozle-assisted Learning Media is declared feasible, practical, and effective to use in learning.